Citrus peel oil deterpenation with supercritical fluids: Optimal process and solvent cycle design - Díaz, María Soledad (2005)
In this work supercritical deterpenation of orange peel oil with carbon dioxide is studied. Optimal schemes and operating conditions are determined through the formulation of a nonlinear programming model that includes reliable thermodynamic predictions with a group contribution equation of state and rigorous unit models. A detailed comparison of binary and ternary equilibrium predictions with available experimental data is reported. Simulation results are in agreement with previous laboratory-scale separation values. Different solvent cycle schemes have been included in the mathematical model. Net profit is maximized taking into account capital and operating costs associated to the complete deterpenation process. Numerical results show that a compression cycle is the optimal solvent recovery system in all cases. Furthermore, optimal operating conditions have been determined in main units (extractor and separator), for the production of both a five-fold concentrate and a high purity aroma, as raffinate, respectively.